2021
DOI: 10.1186/s12865-021-00417-9
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory receptor Tim-3 fails to suppress IFN-γ production via the NFAT pathway in NK-cell, unlike that in CD4+ T cells

Abstract: Background T cell immunoglobulin and mucin domain-containing-3 (Tim-3) is a negative regulator expressed on T cells, and is also expressed on natural killer (NK) cells. The function of Tim-3 chiefly restricts IFNγ-production in T cells, however, the impact of Tim-3 on NK cell function has not been clearly elucidated. Results In this study, we demonstrated down-regulation of Tim-3 expression on NK cells while Tim-3 is upregulated on CD4+ T cells dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Lisovsky et al reported that blockade of NKG2A in vitro increases CD56 dim NKG2A pos NK cell degranulation and secretion of IFN-g and CCL4 against infected CD4 T cells (120). As mentioned in Section Surface Receptor Imbalance Weakens NK Cell Functions blockade of immune checkpoints such as Siglec-9, TIGIT, PD-1, and Tim-3 also enhance the killing activity of NK cells in HIV infection (28,38,44,49). Inhibitors of NK cell inhibitory receptors might thus prove useful for promoting NK cell functions in HIV infection.…”
Section: Blocking Inhibitory Receptors For Nk Cell Functionmentioning
confidence: 97%
See 2 more Smart Citations
“…Lisovsky et al reported that blockade of NKG2A in vitro increases CD56 dim NKG2A pos NK cell degranulation and secretion of IFN-g and CCL4 against infected CD4 T cells (120). As mentioned in Section Surface Receptor Imbalance Weakens NK Cell Functions blockade of immune checkpoints such as Siglec-9, TIGIT, PD-1, and Tim-3 also enhance the killing activity of NK cells in HIV infection (28,38,44,49). Inhibitors of NK cell inhibitory receptors might thus prove useful for promoting NK cell functions in HIV infection.…”
Section: Blocking Inhibitory Receptors For Nk Cell Functionmentioning
confidence: 97%
“…Yu et al. reported reduced Tim-3 expression on NK cells in HIV-infected individuals ( 49 ), and de Kivit et al. reported reduced Tim-3 expression on NK cells in HIV immunologic non-responders compared with immunologic responders.…”
Section: Nk Cell Dysfunction During Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TIM-3 is a marker of T cell exhaustion ( 153 ), its expression is not associated with NK cell dysfunction in healthy donors. TIM-3 is also expressed in NK cells, the cytolytic activity of TIM-3 + NK cells from healthy humans is higher than that of TIM-3 - NK cells, and the TIM-3 + NK cells can kill K562 cells by releasing IFN-γ ( 158 160 ).…”
Section: Car-nk Cell and Immune Checkpoint Therapiesmentioning
confidence: 99%
“… 40 , 68 Overall, the functional significance of TIM3 upregulation on several tumor-infiltrating T and innate cells, such as NK cells and dendritic cells (DCs), within tumors is still to be completely defined. 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 …”
Section: Introductionmentioning
confidence: 99%